2015
DOI: 10.3109/10826084.2014.997391
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use by Egyptian Youth: Current Patterns and Potential Avenues for Prevention

Abstract: These findings will inform the design of quantitative surveys aimed at estimating the prevalence of specific behaviors related to substance use among youth and potential avenues for prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 25 publications
5
34
2
Order By: Relevance
“…Loffredo et al Classified these factors into: 1) intrinsic factors such as health reasons and self-esteem, and 2) extrinsic factors such as religious beliefs, family influences, and prevention messages of control programmes. The influence of these factors needs to be further investigated and exploited to enhance prevention programs (27).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Loffredo et al Classified these factors into: 1) intrinsic factors such as health reasons and self-esteem, and 2) extrinsic factors such as religious beliefs, family influences, and prevention messages of control programmes. The influence of these factors needs to be further investigated and exploited to enhance prevention programs (27).…”
Section: Risk Factorsmentioning
confidence: 99%
“…26 Friends are an important source for such misuse, where peer pressure from friends, or having a family member who used them, stood out as the most common reason to start and continue using substances. 10,17,18 Gender differences were observed in abuse of psychotropic medications. Female sex was associated with increased likelihood of benzodiazepine use.…”
Section: Sources and Reasons For Sm Abusementioning
confidence: 99%
“…10 94.1% of pharmacists suspected that some level of abuse/misuse occurred in their pharmacy, which was highest for decongestants, cough/cold preparations. 1 Swaileh et al reported that antitussives, analgesics, antihistamines, and laxatives were identified by pharmacists as misused and abused medications.…”
Section: Cough/cold Products and Laxativesmentioning
confidence: 99%
See 2 more Smart Citations